Complex permittivity measurement using capacitance method from 300 kHz to 50 MHz - Raymond W.J.K.; Chakrabarty C.K.; Hock G.C.; Ghani A.B. (Elsevier B.V., 2023)
Complex permittivity measurement has been performed using a parallel plate capacitor and a vector network analyzer (VNA) from 300 kHz to 50 MHz. The material under test (MUT) is a flat and thin sample clamped between the capacitor plates and connected to the VNA to obtain its two port S parameters. The S parameter is converted into impedance to calculate the complex permittivity using Matlab program. Techniques used to overcome the air gap and stray capacitance was described. Measurement obtained using the proposed method was compared with the free space method to validate its accuracy. The percent difference is less than 5%. 2013 Published by Elsevier Ltd.